1976
DOI: 10.1007/bf01920770
|View full text |Cite
|
Sign up to set email alerts
|

NMR-Studies of triiodothyropropionic acid in ethanol-HCl

Abstract: The barrier to rotation in the N-acetyl methyl ester of the thyroxine was found to be 8.6 kcal mol-1. Previous experiments determining the barrier to rotation in triiodothyropropionic acid in HCl-ethanol were shown to be in error.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1978
1978
1997
1997

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Knowledge of this three-dimensional shape provides a starting point for modeling the interactions of the hormones with their target proteins, but the representation shown in Figure a is somewhat simplified, because it is known that there are significant dynamic motions associated with the outer ring. Studies on soluble analogues, , and later on T4 and T3 themselves, have shown that rotation about the diphenyl ether linkage with a barrier of approximately 36 kJmol -1 produces an interchange of the environment of H2‘ with that of H6‘. For hormones which are symmetrically iodinated in the outer ring, the interchange occurs between isoenergetic (and structurally equivalent) forms, but for monoiodinated derivatives such as T3, the rotation about the diphenyl ether linkage interconverts “proximal” and “distal” forms of the hormone, as illustrated in Figure .…”
Section: Introductionmentioning
confidence: 99%
“…Knowledge of this three-dimensional shape provides a starting point for modeling the interactions of the hormones with their target proteins, but the representation shown in Figure a is somewhat simplified, because it is known that there are significant dynamic motions associated with the outer ring. Studies on soluble analogues, , and later on T4 and T3 themselves, have shown that rotation about the diphenyl ether linkage with a barrier of approximately 36 kJmol -1 produces an interchange of the environment of H2‘ with that of H6‘. For hormones which are symmetrically iodinated in the outer ring, the interchange occurs between isoenergetic (and structurally equivalent) forms, but for monoiodinated derivatives such as T3, the rotation about the diphenyl ether linkage interconverts “proximal” and “distal” forms of the hormone, as illustrated in Figure .…”
Section: Introductionmentioning
confidence: 99%
“…The outer ring proton which is proximal to the inner ring is upfield of the distal proton, due to a significant ring current shift. For T4, T3, and several analogues , the barrier to the conformational exchange of H2‘ and H6‘ ranges from 33 to 38 kJ mol -1 .
2 Interconversion of the distal and proximal protons of T4.
…”
Section: Introductionmentioning
confidence: 99%